2023
DOI: 10.1039/d2nr07018a
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng-derived exosome-like nanovesicles extracted by sucrose gradient ultracentrifugation to inhibit osteoclast differentiation

Abstract: Ginseng-derived extracellular nanovesicles effectively blocked bone loss both in vitro and in vivo by inhibiting osteoclast differentiation through RANKL-induced IκBα, JNK, and ERK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the majority of studies (61% or 17/28 studies), exosomes were isolated from humans; additionally, exosomes were isolated from mice in 6 studies (primarily RAW264.7 cells), rats in 4 studies (primarily rat BMSCs) and plant‐based exosomes in one study (ginseng). All target cells examined in vitro demonstrated the stimulatory effects of exosomes on osteogenic differentiation, with the exception of research conducted by Seo et al., 41 who investigated the impact of bone marrow‐derived macrophages on osteoclast inhibition by exosomes. The target tissue was BMSCs in 27/28 studies, of which 12 were performed on human BMSCs, whereas 7 studies were performed on rats and 9 were performed on mice.…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of studies (61% or 17/28 studies), exosomes were isolated from humans; additionally, exosomes were isolated from mice in 6 studies (primarily RAW264.7 cells), rats in 4 studies (primarily rat BMSCs) and plant‐based exosomes in one study (ginseng). All target cells examined in vitro demonstrated the stimulatory effects of exosomes on osteogenic differentiation, with the exception of research conducted by Seo et al., 41 who investigated the impact of bone marrow‐derived macrophages on osteoclast inhibition by exosomes. The target tissue was BMSCs in 27/28 studies, of which 12 were performed on human BMSCs, whereas 7 studies were performed on rats and 9 were performed on mice.…”
Section: Resultsmentioning
confidence: 99%
“… 26 These methods involve extracting ELNs from plant tissues or cell cultures, followed by meticulous separation approaches such as differential centrifugation, ultrafiltration, or precipitation methods. 27 The choice of isolation method depends on factors such as desired yield, purity, and specific downstream applications, ensuring the procurement of well-defined plant ELN populations.…”
Section: Properties and Characteristics Of Plant Elnsmentioning
confidence: 99%
“…Bone tissue engineering has emerged as a promising approach for repairing and regenerating damaged or lost bone tissue, and plant ELNs offer unique properties that make them attractive for promoting bone regeneration. 27 The small size, biocompatibility, and cargo-carrying capabilities of plant ELNs contribute to their potential in this field.…”
Section: Application Of Plant Elns In Promotion Of Different Tissue R...mentioning
confidence: 99%
“…EVs secreted by plants contain mRNAs, proteins, miRNAs, and bioactive lipids with unique and diverse pharmacological mechanisms that can exert multiple effect, such as antioxidant, anti-inflammatory, and antiosteoporotic effects. Studies have reported that EVs isolated from yams, 164 ginseng, 165 plums, 166 and apples. 167 have antiosteoporotic effects.…”
Section: The Potential Role Of Evs Derived From Different Sources In ...mentioning
confidence: 99%